2018
DOI: 10.3390/su10041234
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Sustainable Use of the Fish Resources from Lake Balkhash, a Fragile Lake in an Arid Ecosystem

Abstract: Lake Balkhash is the largest water body in Central Asia. More than three-quarters of its inflow comes from the Ili River, which is under increasing strain due to the diversion of water for energy and food production. Commercial fishing in Lake Balkhash began in 1929 and is currently in a state of crisis. The construction of the Balkhash dam and reservoir in the late 1960s reduced Ili River flows into the lake and upset the natural cycle of spring floods, which greatly reduced spawning and feeding areas for car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Flow regulation in the lower reaches of the Ili River after the Kapchagay reservoir dam construction, high water pollution with organic and heavy metals, overfishing and poaching impact on ecosystem of the western Balkhash have long history. This was recently traced in several publications that reported escalation of negative loading on the ecosystem (Graham et al, 2017;Krupa et al, 2020;Mischke et al, 2020;Pueppke et al, 2018;Sala et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Flow regulation in the lower reaches of the Ili River after the Kapchagay reservoir dam construction, high water pollution with organic and heavy metals, overfishing and poaching impact on ecosystem of the western Balkhash have long history. This was recently traced in several publications that reported escalation of negative loading on the ecosystem (Graham et al, 2017;Krupa et al, 2020;Mischke et al, 2020;Pueppke et al, 2018;Sala et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Williams et al (2009) reported that some rare species could avoid extinction if they were sufficiently generalist to utilize suboptimal habitat types The Balkhash perch is just such species that can use various foods and use different life strategies (Mamilov, 2016). The high pressure of legal fishery and poaching on most abundant introduced commercial fish species lead to decrease of total number of fish and harvest (Pueppke et al, 2018), but it gave ecological space to the indigenous one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the old legal framework began to dissolve and enforcement was relaxed, agriculture entered a period of decline such that by 1999, fully half of all food production in the new republics had been wiped out [96]. Yields from aquaculture facilities (some near Kapchagai Reservoir) and of fish captured in the lake were especially hard hit [45,48], as lax management, insufficient regulation of water withdrawals, and overuse of water resources took their toll [14,48,56,57,97]. Sharp reductions in livestock numbers [28] paralleled the decline in capture fisheries, as provision of water for pastures was curtailed [98] and the newly-independent states struggled to become self-sufficient rather than specialized in the production of sheep, goats, and cattle [99].…”
Section: Geopolitical Determinantsmentioning
confidence: 99%
“…Given the harshness of the environment and lack of water, it is not surprising that the 37,400 km 2 Balkhash District contains just 30,700 inhabitants who live mainly in 34 settlements near lakes and streams. The region's economic activity emphasizes pasture-based animal husbandry, recreational and commercial fishing, and extraction of minerals, and it is based on maximum exploitation of water and other natural resources [24][25][26][27]. Due to the extremely arid climate and high energy costs, irrigation for agriculture is only possible in two small gravity-fed areas near the Ili River (Figure 1).…”
Section: Introductionmentioning
confidence: 99%